Determination Yield Sukuk: Sukuk Risks, Fiscal Policy With The Mediation Role Of Sukuk Value On The Indonesian Stock Exchange - Yusrialis (MUI Kota Pekanbaru, 2025)
This study analyzes the effect of sukuk risk and fiscal policy on sukuk yield with sukuk value as a mediating variable on the Indonesia Stock Exchange for the 2020–2024 period. The study uses a quantitative approach with a purposive sampling technique on corporate sukuk with mudharabah contracts. The results show that sukuk risk has a significant positive effect on sukuk yield, while fiscal policy has a significant negative effect. Sukuk value is proven to mediate the relationship between risk and fiscal policy on sukuk yield. The Sobel Test shows that both independent variables (X1 and X2) have significant mediation by M (Sukuk Value), thus supporting the research hypothesis that risk/fiscal policy does not directly affect yield, but through sukuk value, for example, high risk reduces the outstanding value, which increases yield to attract investors. This study contributes to the development of Islamic finance literature, particularly in integrating the mediating role of sukuk value in the Indonesian capital market.